2000
DOI: 10.1016/s0002-9297(07)62959-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a cDNA Representing the Fanconi Anemia Complementation Group E Gene

Abstract: Fanconi anemia (FA) is an autosomal recessive chromosomal instability syndrome with at least seven different complementation groups. Four FA genes (FANCA, FANCC, FANCF, and FANCG) have been identified, and two other FA genes (FANCD and FANCE) have been mapped. Here we report the identification, by complementation cloning, of the gene mutated in FA complementation group E (FANCE). FANCE has 10 exons and encodes a novel 536-amino acid protein with two potential nuclear localization signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…The FANCA multiplex quantitative fluorescent PCR (QF-PCR) gene dosage assay used has been previously described by Morgan et al 28 This multiplex amplifies five exons (5,11,17,21, and 31) and uses exon 1 of the myelin protein zero (MPZ) gene as a non-FA gene control. An additional biplex assay that amplifies a 352 bp fragment encompassing both exons 19 and 20 of FANCA and exon 1 of MPZ was also designed (forward 5 0 GAAACACCGGTCACCGTCTGTG 3 0 , reverse 5 0 AGATCCAC-GATTCTTCGCATTGTC 3 0 ).…”
Section: Quantitative Fluorescent Pcr Analysis Of Fanca Gene Dosagementioning
confidence: 99%
See 1 more Smart Citation
“…The FANCA multiplex quantitative fluorescent PCR (QF-PCR) gene dosage assay used has been previously described by Morgan et al 28 This multiplex amplifies five exons (5,11,17,21, and 31) and uses exon 1 of the myelin protein zero (MPZ) gene as a non-FA gene control. An additional biplex assay that amplifies a 352 bp fragment encompassing both exons 19 and 20 of FANCA and exon 1 of MPZ was also designed (forward 5 0 GAAACACCGGTCACCGTCTGTG 3 0 , reverse 5 0 AGATCCAC-GATTCTTCGCATTGTC 3 0 ).…”
Section: Quantitative Fluorescent Pcr Analysis Of Fanca Gene Dosagementioning
confidence: 99%
“…3 A recent survey of cancer incidence in 145 FA patients reported nine cases of myeloid leukemia with a median age-of-onset of 11.3 years, and a ratio of observed to expected cases of 785. 4 Complementation analysis by cell fusion and correction of crosslinker hypersensitivity has delineated at least eight complementation groups; FA-A, B, C, D1, D2, E, F, G, 5 six genes have been cloned, FANCA, C, D2, E, F, G, [6][7][8][9][10][11][12] and a recent report has shown biallelic inactivation of BRCA2 in FA-D1 cell lines. 13 Since the incidence of AML is highly elevated in FA patients, it is possible that inherited or acquired mutations in the FA genes contribute to the etiology of sporadic AML.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 7 FA genes have been cloned, and the sequences of the representative cDNAs for the FANCA, 22,23 FANCC, 24 FANCD2, 25 FANCE, 26 FANCF, 27 FANCG, 28 and FANCD1 (BRCA2) 29 genes are available. QRT-PCR was used to quantify transcripts from each of these genes relative to an internal amplification standard (18S RNA) and also compared with the myeloid cell line Mo7e ( Figure 3).…”
Section: Fa Gene Transcripts Are Quantitatively Normalmentioning
confidence: 99%
“…Seven of the FA genes have been cloned. [22][23][24][25][26][27][28][29] Apart from BRCA2 (the FANCD1 gene), the cloned sequences bear homologies neither to other known genes nor to one another. The FA genes clearly protect cells from genotoxic stress.…”
Section: Genetic Analysis Of a Lymphoblastoid Cell Line From The Samementioning
confidence: 99%
“…Patients may also have congenital malformations including short stature, small gonads, microphthalmia, and skeletal defects (Alter 1993). At least eight complementation groups exist (FA-A through FA-G, including D1 and D2; Joenje et al 1997;Timmers et al 2001), and the genes for seven of these have been identified (FANCA, FANCC, FANCD2, FANCE, FANCF, FANCG, and BRCA2;Strathdee et al 1992;Lo Ten Foe et al 1996;de Winter et al 1998de Winter et al , 2000aTimmers et al 2001;Howlett et al 2002).…”
mentioning
confidence: 99%